Eco-friendly and economical dyeing of double-sided cotton/polyester fabric (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
This study has been carried out to dye double-sided cotton/polyester fabric by single bath method, with disperse and reactive dyes, without draining out the liquor after polyester side dyeing and with no extra chemicals. Three different dyeing procedures (two-bath two-step, one-bath two-step and one-bath one-step) have been used. The findings were evaluated in terms of dyebath exhaustion (E) and color strength (K/S) parameters. The experimental dyebath exhaustion values are found acceptable and fit well with the exponential model. Color strength for the one-bath dyeing procedures is found comparable with those of the two-bath method. The performed one-bath dyeing method is found more productive and environment friendly as compared to two-bath technique, because it saves the consumption of water, energy, time and chemicals.